Domain of a yeast site-specific recombinase (Flp) that recognizes its target site. - Chen, J W (1991)
Binding of a partial proteolytic digest by V8 enzyme of the yeast site-specific recombinase Flp to its target site gives rise to DNA-protein complexes that are smaller than those produced by the full-sized protein. The smallest of these complexes (occupancy of one peptide monomer per site) contains either one of two polypeptides (32 and 28 kDa) of the V8 digestion mixture. The amino termini of both polypeptides map to Ser-129 of Flp, corresponding to V8 cleavage at Glu-128. The relative mobilities of the complexes formed by the V8 peptides indicate that they lack the sharp substrate bend that is characteristic of Flp-derived complexes. A hybrid protein consisting of the amino-terminal one-third of the R recombinase (from Zygosaccharomyces rouxii) and the carboxyl-terminal two-thirds of Flp recognizes the Flp target site.